Problems of Reforms of Education in Turkestan - Khamidovna, Ziyaeva Dono (International Journal of Psychosocial Rehabilitation, 2020)
In this article, the cultural life of the Turkestan is widely illustrated in the example of the educational system in the second half of the 19 century – the beginning of the 20 centuries. The introduction of full information about schools and madrassas, which were considered parts of traditional education, pedagogical process in them, detailed information on their educational activities, provision, the list of subjects to be taught, as well as textbooks gives a chance to acquire whole information on the issue. Besides, the author studied the problems existing in educational system of that period and analyzed the ways of their elimination. In this regard, there has been highlighted the role of education in society, the opportunities created for students and teachers, the unique role of the education system in the cultural life of society in the article.